2016
DOI: 10.1007/s10726-016-9511-9
|View full text |Cite|
|
Sign up to set email alerts
|

Drivers of Durable Peace: The Role of Justice in Negotiating Civil War Termination

Abstract: Attaining durable peace after a civil war has become a major challenge, as many negotiated settlements relapse into violence. How can civil war negotiations be conducted and peace agreements formulated so as to contribute to lasting, durable peace? Previous research has focused on the durability of peace agreements, measured as the absence of violence. This study develops an index to measure durable peace for a period of 8 years after the agreement had been reached, and evaluates the new measure using an exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Thus, adhering to PJ principles during the process of negotiating should contribute to peace following the agreement. Indeed, strong correlations between PJ and DP were found in the sixteen cases analyzed by Wagner and Druckman (2017). The relationship was strongest on the reconciliation component of the DP index (r ¼ .66).…”
Section: Pjmentioning
confidence: 89%
See 2 more Smart Citations
“…Thus, adhering to PJ principles during the process of negotiating should contribute to peace following the agreement. Indeed, strong correlations between PJ and DP were found in the sixteen cases analyzed by Wagner and Druckman (2017). The relationship was strongest on the reconciliation component of the DP index (r ¼ .66).…”
Section: Pjmentioning
confidence: 89%
“…In their field studies of mediation, Pruitt et al (1993) reported that PJ judgments were a stronger predictor of improved relations with the other party (SA) than goal achievement or satisfaction with the agreement. Adherence to PJ principles also increased perceptions of the legitimacy of agreements in felony cases (Casper, Tyler, and Fisher 1988) and with the cessation of violence in civil wars (Albin and Druckman 2012;Wagner and Druckman 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The R script that we have developed as supplementary material for this paper was conceived as an example that can be followed by other scientists interested in exploring the documents of Colombia, Guatemala and El Salvador where the need to understand the social mechanisms leading to permanent violence has been commonly highlighted (McDougall, 2009;Preti, 2002;Bourgois, 2001). Given the fact that peace agreements often include sensitive issues for reestablishing justice and governance (Wagner & Druckman, 2016), text mining techniques in general and readability evaluations in particular, are useful for assessing the difficulty of these texts and clarify the order of peace implementation that prove to be a key ingredient for reducing destabilizing effects of post-accord elections (Joshi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The durable peace index that we constructed for our research consists of four components: reconciliation, security institutions, governance, and economic stability or growth. We tested the durable peace index and found that the durability found in the earlier studies mediates the relationship between the equality provisions in the peace agreements and the longer-term, durable peace (Wagner & Druckman, 2017).…”
Section: Introductionmentioning
confidence: 93%